Comparison of Short-Term Outcomes of Transcatheter versus Surgical Closure of Atrial Septum Defect at a Tertiary Cardiac Care Facility - Saleem, Shoaib; Younas, Muhammad; Asma, Tauseef; Riaz, Usman; Tousif, Rubina; Maqbool, Baqir (Pakistan Armed Forces Medical Journal, 2023)
Objective: To compare the short-term outcomes of transcatheter versus surgical closure of atrial septal defect (ASD) at a tertiary cardiac care facility in South Punjab, Pakistan.Study Design: Prospective comparative study.Place and Duration of the Study: Department of Paediatric Cardiology and Paediatric Cardiac Surgery, Chaudhary Pervez Elahi Institute of Cardiology, Multan Pakistan, from Jul 2019 to Jun 2021.Methodology: A total of 110 patients with moderate to large isolated secundum ASDs without severe pulmonary hypertension and planned to undergo closure of secundum ASD by either surgical approach or device closure were included. All surgical and transcatheter procedures were performed adopting standard techniques. Intra-procedural or post-procedural outcomes were noted.Results: In a total of 110 patients, 59(53.6%) underwent transcatheter closure of ASD, while surgical closure was done in the remaining 51(46.4%) patients. Post-procedural complications were significantly more in the Surgical Closure Group in comparison to the Transcatheter Closure Group, [14(27.5%) vs 5(8.5%) (p=0.026)]. None of the cases in the Transcatheter Closure Group required inotropes in the post-procedure period in comparison to 24(47.1%) cases (p